2-Dimensional rare earth metal–organic frameworks based on a hexanuclear secondary building unit as efficient detectors for vapours of nitroaromatics and volatile organic compounds. Issue 19 (22nd June 2022) - Panagiotou, Nikos; Moscoso, Francisco García; Lopes-Costa, Tânia; Pedrosa, José María; Tasiopoulos, Anastasios J.
Abstract : A new family of microporous 2-dimensional rare earth metal organic frameworks based on a hexanuclear secondary building unit with capability to selectively detect vapours of volatile organic compounds and nitroaromatic explosives is reported. Abstract : The synthesis, characterisation and capability to selectively detect vapours of volatile organic compounds (VOCs) and nitroaromatic explosives of a new family of 2-dimensional rare earth (RE) MOFs based on a hexanuclear (RE 3+ )6 secondary building unit (SBU) is reported. The reaction of RE(NO3 )3 with 4, 4′-sulfonyldibenzoic acid (H2 SDBA) in the presence of 2-fluorobenzoic acid (HFBA) in DMF/MeOH at 100 °C afforded compound [RE6 (μ3 -OH/F)8 (SDBA)4 (NO3 )2 (H2 O)6 ] n (UCY-15 (RE); RE: Y, Eu, Gd, Tb, Dy, Ho, Er). The structure of UCY-15 (RE) comprises a microporous 8-connected 2D network based on a (RE 3+ )6 SBU and the angular dicarboxylate ligand SDBA 2− and contains rhombic channels along b and c axes. Gas sorption studies on activated UCY-15 (Y) indicated a moderate BET surface area of 417 m 2 g −1 . Photoluminescence (PL) studies in the visible region of UCY-15 (RE) (RE: Y, Eu, Gd, Tb) revealed that SDBA 2− is able to sensitize Eu 3+ and Tb 3+ ions. Thin films of UCY-15 (RE) (RE: Y, Eu, Tb) embedded in polydimethylsiloxane (PDMS) were fabricated and evaluated for their sensing capability for vapours of selected VOCs and nitroaromatic compounds revealing different response to each analyte tested. A series of trimetallic analogues UCY-15 (Y100− x − y Eu x Tb y ) ( x, y = 5, 7.5, 10) were prepared aiming to superior sensing materials that combine the PL signals of UCY-15 (Y), UCY-15 (Eu) and UCY-15 (Tb). The analogue UCY-15 (Y87.5 Eu7.5 Tb5 ) achieved the emission of white light whereas UCY-15 (Y87.5 Eu5 Tb7.5 )@PDMS films were shown to selectively recognize the tested analytes. Overall, this work highlights the capability of microporous 2D MOFs containing highly accessible emissive centers to recognise vapours of selected analytes.